Turning waste into wealth Success story of a vermicomposting venture - Buttar, Tejbir Singh; Singh, Vinay; Singh, Gurdeep (Indian Farming, 2024)
Jagdeep Singh, a farmer from Bathinda, Punjab, transformed his 2 acre ancestral land into a thriving vermicomposting business. Starting in 2014 with just 4 vermibeds, he expanded to 208 beds by 2023, producing 3,120 quintals of vermicompost annually and earning `22.27 lakh per year. With support from Punjab Agricultural University’s Krishi Vigyan Kendra, he implemented innovative practices like a self-installed sprinkler system and cucurbit plants for shade. His brand, 'Harpreet Organic Manure,' gained recognition across Punjab and neighbouring states. This venture uplifted his family's standard of living, created rural jobs, and inspired others to adopt sustainable farming practices, showcasing how resilience and innovation can drive community development and environmental sustainability.